Durometry in SSc: The hard facts. A systematic literature review and additional pilot study. (4th February 2021) - Vanhaecke, Amber; Verschuere, Sven; Vilela, Veronica; Heeman, Lise; Cutolo, Maurizio; Smith, Vanessa
Abstract: Objectives: To investigate the reliability of durometry in systemic sclerosis (SSc), by means of a systematic review and additional pilot study. Methods: Literature was systematically reviewed according to the PRISMA guidelines to identify all original studies assessing the reliability of durometry in SSc. Additionally, in the pilot study, intra-rater reliability was evaluated in a first cohort of 74 SSc patients (61 female, 13 LSSc/53 LcSSc/8 DcSSc). In a second separate set of 30 SSc patients (21 female, 4 LSSc/20 LcSSc/6 DcSSc), intra- and inter-rater reliability were evaluated. Results: Only two unique records identified through the systematic review were qualified to generate conclusions. Regarding intra-rater reliability, Kissin reported excellent intra-class correlation coefficient values (ICC, 0.86–0.94) for measurements at nine skin sites in two DcSSc patients. Merkel and Kissin described, both in five DcSSc patients, good to excellent inter-rater reliability (ICC, 0.82–0.96 and 0.61–0.85) for measurements at respectively, six and nine skin sites. In our pilot study, ICC for intra-rater reliability at 17 standardized skin sites were excellent in both cohorts, ranging 0.93–0.99 and 0.78–0.98, respectively. ICC for inter-rater reliability at 17 standardized skin sites were good to excellent 0.63–0.93, except for the feet (0.48 and 0.52). Conclusion: The preliminary findings in the literature are supported by our pilot study in which we have attested the reliability of durometry in SSc patients. However, prior to including durometry as an (additional) outcome measure in SSc clinical trials, its validation status in the assessment of skin fibrosis needs to be completely attested.